FENOMENA PENYERTAAN NILAI (MEDIT) DALAM MENENTUKAN HARGA BELI PENGEPUL RONGSOKAN - Rahmansyah, Ahmad Iskandar; Suharsono, Judi; Musriati, Titik (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
This study aims to explore the concept of determining the buying price for scrap collectors because based on previous research studies there is a phenomenon that information is obtained that the inclusion of non-economic values determines the purchase price of certain products. Researchers chose junk collectors as the object of research because junk collectors are known to have entrepreneurial characteristics. The transcendental phenomenon is used to execute research purposes. The results showed that in determining the purchase price, the junk collector used the inclusion of a non-economic value, namely Medit (Stingy). This value is included in the formation of the purchase price as a form of feeling for junk which is a dirty item and is also not used but is profitable so it should not be negotiable because it can be seen from the stigma of the community who still think that the business of scrap collector is dirty and even considered a person who does not have skills for other work.